2021
DOI: 10.1002/cb.1978
|View full text |Cite
|
Sign up to set email alerts
|

The nature of peer‐initiated brand communities on social media platforms

Abstract: In the recent years, consumers are increasingly engaging in dynamic interactions with their preferred brands through online brand communities. Although Facebook has been commonly used as the social media platform for online brand communities, less is known with respect to the success factors for these brand communities. This study examines the nature of peer‐initiated brand communities by proposing and testing a conceptual framework that encompasses brand community identity, brand community engagement, brand l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…We argue that displays of luxury in individuals with high levels of CBE should lead to identification with the brand user, which in turn should enhance more positive evaluation of the brand user. This mechanism is based on the insight that people engaged in a brand form a kind of a social group (Bagozzi & Dholakia, 2006; Hook et al, 2020; Wong, 2021), and this group membership results in a more positive evaluation of the group members (Tajfel & Turner, 2004). Thus, we added to the growing body of literature on this topic by showing that identification with the brand user is important in understanding how individuals perceive luxury brand users.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that displays of luxury in individuals with high levels of CBE should lead to identification with the brand user, which in turn should enhance more positive evaluation of the brand user. This mechanism is based on the insight that people engaged in a brand form a kind of a social group (Bagozzi & Dholakia, 2006; Hook et al, 2020; Wong, 2021), and this group membership results in a more positive evaluation of the group members (Tajfel & Turner, 2004). Thus, we added to the growing body of literature on this topic by showing that identification with the brand user is important in understanding how individuals perceive luxury brand users.…”
Section: Discussionmentioning
confidence: 99%
“…In today's society, the role of emblems indicating belonging is played by the brand and the degree to which it is exposed to others (brand prominence; Butcher et al, 2016; Han et al, 2010). Research has indicated that membership to groups may be derived from brand ownership or attitude toward a brand (Bagozzi & Dholakia, 2006; Hook et al, 2020; Wong, 2021). In this context, the visible logo acts as a signal sent to other members of society indicating group affiliation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The marketing discipline has mostly considered the use of social media favorably in terms of meeting the needs of consumers and business objectives through research and pedagogy. Significant work in the Journal of Consumer Behaviour investigates opportunities to increase consumers' engagement with (Devereux et al, 2020; Heinonen, 2011; Hofmann et al, 2021; Wong, 2021), attitudes toward (Chen & Qasim, 2021; Chu & Chen, 2019; Lim et al, 2021), and trust in brands in social media environments (Carlson et al, 2021; Upadhyay et al, 2022). Less work has evaluated when consumers are pulling away from social media.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the rise in proactive consumers, or prosumers, the generation of continuous consumer–brand conversations fortifies the core of the value co-creation process (Lawer and Knox, 2006). The recent surge in disruptive technologies has enabled efficient socializing in consumer-initiated OBCs, which allowed firms to tune in to their customers’ voice and understand their changing demands to achieve online brand advocacy (Wong, 2021). This new phenomenon in consumer-initiated OBCs has propelled the need for further investigation into how and why consumers advocate for brands online (Wilk et al , 2021).…”
Section: Introductionmentioning
confidence: 99%